Can patients with chronic fatigue syndrome really recover after graded exercise or cognitive behavioural therapy? A critical commentary and preliminary re-analysis of the PACE trial. Issue 1 (2nd January 2017) - Wilshire, Carolyn; Kindlon, Tom; Matthees, Alem; McGrath, Simon
ABSTRACT: BACKGROUND : Publications from the PACE trial reported that 22% of chronic fatigue syndrome patients recovered following graded exercise therapy (GET), and 22% following a specialised form of CBT. Only 7% recovered in a control, no-therapy group. These figures were based on a definition of recovery that differed markedly from that specified in the trial protocol. PURPOSE : To evaluate whether these recovery claims are justified by the evidence. METHODS : Drawing on relevant normative data and other research, we critically examine the researchers' definition of recovery, and whether the late changes they made to this definition were justified. Finally, we calculate recovery rates based on the original protocol-specified definition. RESULTS : None of the changes made to PACE recovery criteria were adequately justified. Further, the final definition was so lax that on some criteria, it was possible to score below the level required for trial entry, yet still be counted as 'recovered'. When recovery was defined according to the original protocol, recovery rates in the GET and CBT groups were low and not significantly higher than in the control group (4%, 7% and 3%, respectively). CONCLUSIONS : The claim that patients can recover as a result of CBT and GET is not justified by the data, and is highly misleading to clinicians and patients considering these treatments.